2006
DOI: 10.1016/j.ydbio.2006.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Pitx2 regulates cardiac left–right asymmetry by patterning second cardiac lineage-derived myocardium

Abstract: Current models of left-right asymmetry hold that an early asymmetric signal is generated at the node and transduced to lateral plate mesoderm in a linear signal transduction cascade through the function of the Nodal signaling molecule. The Pitx2 homeobox gene functions at the final stages of this cascade to direct asymmetric morphogenesis of selected organs including the heart. We previously showed that Pitx2 regulated an asymmetric pathway that was independent of cardiac looping suggesting a second asymmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 55 publications
10
98
0
Order By: Relevance
“…These Pitx2 ϩ /myogenin Ϫ cells may be either surface ectoderm or neural crest derivatives. Pitx2 expression in neural crest derivatives has also been observed in other regions of the head (20)(21)(22)(23). Pitx2 expression was generally not observed in nonmyogenic territories surrounding anlagen in other regions of the body (17) Severe losses in myogenin ϩ /Pitx2 ϩ territories were observed in the region adjacent to the tongue that represents the vestigial jaw ( Fig.…”
Section: Pitx2 Is Required For Initiation Of Myogenic Progression In mentioning
confidence: 90%
“…These Pitx2 ϩ /myogenin Ϫ cells may be either surface ectoderm or neural crest derivatives. Pitx2 expression in neural crest derivatives has also been observed in other regions of the head (20)(21)(22)(23). Pitx2 expression was generally not observed in nonmyogenic territories surrounding anlagen in other regions of the body (17) Severe losses in myogenin ϩ /Pitx2 ϩ territories were observed in the region adjacent to the tongue that represents the vestigial jaw ( Fig.…”
Section: Pitx2 Is Required For Initiation Of Myogenic Progression In mentioning
confidence: 90%
“…We determined that direction of heart looping is specified at approximately the seven-somite stage in the chick (Linask et al, 2005a) and suggested that the asymmetry of cell proliferation and flectin in the anterior heart field may relate to asymmetric patterning of Pitx2c (Ai et al, 2006). The laterality gene Nodal in all vertebrates analyzed shows a left expression in the embryo and heart fields and is upstream of Pitx2c.…”
Section: Reduced Asymmetric Nodal Activity Leads To Abnormal Looping mentioning
confidence: 96%
“…The bicoid type homeobox gene pitx2 is expressed in the left side of several organ primordia and has an instructive role in mediating left-right organ asymmetries (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). During female chick gonad development, pitx2c mRNA transcripts are restricted to the presumptive left gonad cortex epithelia at stage 14 HH (Fig.…”
Section: Subcellular Asymmetries Of the Left Versus Right Female Chicmentioning
confidence: 99%
“…Unlike other asymmetric genes, pitx2 expression is maintained during the development of several organ primordia, making it a good candidate to be involved in both mediating the maintenance of left-right information from the lateral plate mesoderm to its derived developing organs and executing it at a cellular level. Indeed, Pitx2 loss-and gain-of-function experiments can cause organ-specific laterality defects in all vertebrates analyzed to date (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).Notwithstanding these advances, we are still far away from understanding how organ primordia interpret left-right genetic information during organogenesis, i.e., how broad domains of side-specific gene expression in the lateral plate mesoderm translate to asymmetric organ development. Moreover, our knowledge on how asymmetric gene activity is linked to specific cellular processes is also still scarce.…”
mentioning
confidence: 99%